2012
DOI: 10.1590/s1519-69842012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Geographical patterns and partition of turnover and richness components of beta-diversity in faunas from Tocantins river valley

Abstract: There has been a resurging interest in patterns of β-diversity, especially by the mechanisms driving broad-scale, continental and global patterns, and how partitioning β-diversity into richness (or nestedness) and turnover components can be linked with such mechanisms. Here we compared two recent methodologies to find richness and turnover components of β-diversity, using a large regional scale dataset of mammal, bird, reptiles and amphibian species found in seven regions of Central, North and Northeastern Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…However, very little is known about the relative importance of ecological variables influencing beta diversity facets and their components, as partitioning facets of beta diversity appeared only recently (Cardoso et al., 2014; Podani & Schmera, ). To date, most of the studies have focused on species‐based beta diversity patterns (Carvalho et al., ; Dobrovolski, Melo, Cassemiro, & Diniz‐Filho, ; Tonial et al., ), while few studies have focused on a multi‐faceted beta diversity approach and their respective components in aquatic macroinvertebrates (but see Heino & Tolonen, ). Our study emphasized the relative importance of local environmental conditions, followed by spatial variables, in explaining variation in all facets of beta diversity and their components (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known about the relative importance of ecological variables influencing beta diversity facets and their components, as partitioning facets of beta diversity appeared only recently (Cardoso et al., 2014; Podani & Schmera, ). To date, most of the studies have focused on species‐based beta diversity patterns (Carvalho et al., ; Dobrovolski, Melo, Cassemiro, & Diniz‐Filho, ; Tonial et al., ), while few studies have focused on a multi‐faceted beta diversity approach and their respective components in aquatic macroinvertebrates (but see Heino & Tolonen, ). Our study emphasized the relative importance of local environmental conditions, followed by spatial variables, in explaining variation in all facets of beta diversity and their components (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The region of the coastline where low biodiversity community composition changes to highly biodiverse communities is reflected in the β-diversity, which peaks around the Cape Peninsula (16/17). Correlations between β-diversity (resulting from a change in α-diversity) and areas of transition have also been noted in several studies on terrestrial biota (Melo et al, 2009;Tonial et al, 2012), but such investigations are less established for marine biota (Schils and Wilson, 2006;Anderson et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…In other words, different components of beta diversity may be driven by different factors (Legendre, ). However, only a handful of recent studies have tested the effects of environment on the different components of beta diversity (Tonial et al ., ; Vad et al ., ; Perez Rocha et al ., ; Victorero et al ., ; Heino et al ., ). These studies have reported contrasting results demonstrating either similar (Perez Rocha et al ., ) or differential (Victorero et al ., ) responses of the two beta diversity components to environmental gradients.…”
Section: Introductionmentioning
confidence: 99%